2021
DOI: 10.3390/environments8010003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ecotoxicity of Soil Affected by Wildfire

Abstract: This study was carried out to assess the ecotoxicity of soil affected by wildfire using two laboratory toxicity tests, and to investigate the possibility of application of selected soil amendment into the burnt soil in order to improve its properties for faster post-fire reclamation. A phytotoxicity test is a fast-indicative test for revealing acute toxicity and was performed on quickly growing plant species Sinapis alba L. and Lepidium sativum L., while a pot experiment is a standardized toxicity test with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The negative impact of diatomite on organisms is not new, as it is used as a natural pesticide in agriculture [ 40 ]. In the study by Borroso et al [ 41 ], an increased plant root inhibition was shown in a 3-day Phytotoxkit assay in sites where diatomite was added to the soil. The observed effect of diatomite therefore seems plausible and, in addition, consistent with the literature [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of diatomite on organisms is not new, as it is used as a natural pesticide in agriculture [ 40 ]. In the study by Borroso et al [ 41 ], an increased plant root inhibition was shown in a 3-day Phytotoxkit assay in sites where diatomite was added to the soil. The observed effect of diatomite therefore seems plausible and, in addition, consistent with the literature [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of soil amendments to burnt soil modifies the soil properties (pH, distribution of substances) and changes the conditions for vegetation recovery [20,21]. Limiting factors of phytoremediation include bad root growth and development in contaminated soil.…”
Section: Discussionmentioning
confidence: 99%
“…Soil amendments can be materials of organic (e.g., compost, biochar) or inorganic (e.g., bentonite, diatomite) origin. Based on previous studies carried out by Barroso et al [20,21], the following organic soil amendments have been chosen here: biochar, compost, a combination of the two, and a combination of biochar and NPK fertilizer with Lolium perenne L., (a grass species that is commonly used for phytoremediation owing to its global geographical distribution in both cold to humid regions). Grass species are used in phytoremediation thanks to properties such as rapid growth, tolerance to contaminants, and the capability to regrow shoots after cutting [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape position or condition can also affect the determination of hydrologic recovery, with some slope aspects having different recovery trajectories and timescales (e.g., Cerda et al, 1995;Kinoshita and Hogue, 2011). Post-fire land management, including treatments to reduce runoff and erosion as well as post-fire logging or site preparation for planting can substantially affect recovery trajectories (e.g., Barroso et al, 2021;Cole et al, 2020;Di Prima et al, 2017;García-Orenes et al, 2017;Kim et al, 2021;Leverkus et al, 2021;Vieira et al, 2018;Wagenbrenner et al, 2015) and may influence the selection of a recovery determination approach. Incorporating anthropogenic stressors (e.g., altered disturbance regimes, habitat conversion and degradation, invasive vegetation species, pollution, see Maxwell et al (2016)) may be essential when assessing functional recovery, especially when projecting hydrologic function of fire-affected watersheds into the future (Kinoshita et al, 2016).…”
Section: Barriers and Challenges For Assessing Post-fire Hydrologic R...mentioning
confidence: 99%